THE EFFECT OF INSERT LEARNING MEDIA ON STUDENS’ READING COMPREHENSION IN RECOUNT TEXT AT THE ELEVENTH GRADE OF SMAN 1 AROSBAYA - Zahroh, Latifah Fatimatuz; -, Dzulfikri; Koher, Saiful (Premise: Journal of English Education and Applied Linguistics, 2022)
The aim of this research was to find out the effectiveness of using Insert learning media to improve reading comprehension at eleventh Grade SMAN 1 Arosbaya. The method used quantitative which was experimental research design. In this research, the researcher chose 13 students as a sample. The result of this research that there was a significant difference in students' reading achievement on recount text before and after being taught using insert learning media, was confirmed. Since the level of significance of the different achievement was not more than 0,025, the different achievement between pre-test and post-test was significant. Meanwhile, the researcher tested the hypothesis by using t-test formula in which the result is 8,06. The total of the participants or the objects of this research was 13 students. Therefore, the degree of freedom is 12 taken by formula df = N – 1. Then, the t-table is 2,18. The score of t-table is higher than the score t-table. As a result, insert learning was an effective medium to improve students reading comprehension especially in recount text because this media can make students easier in comprehending the text.